Correlated ownership: Polanyi, Commons, and the property continuum - Frerichs, Sabine; James, Rick (Research Handbook on the Sociology of International Law, 2018)
According to the economic analysis of law, an efficient property regime is premised on the universality, the exclusivity, and the transferability of property rights. Ideally then, every (legal) person can enjoy the status of an owner and any (economic) resource can become private property; ownership titles could be bought and sold across national jurisdictions and would ultimately be respected everywhere in the world. Throughout history, property regimes indeed seem to have moved towards this ideal. However, this conception of private property is far less natural than it seems, and not without problems. Instead, the institution of property rights is inherently connected with the development of capitalist society, and it reflects the latter’s underlying tensions. The starting point for a sociological account of property rights is to conceive them as a social relation, or a relation of power, which includes (other) owners and non-owners as well as the state as a ‘third party’. In this chapter, the authors build on the work of Karl Polanyi and John R. Commons to suggest that the property regime of the market society relies both on the reification of property (identifying it with the thing owned) and the commodification of the right of ownership (turning it into a marketable commodity). Looking back, the authors retrace how the concept of property changed with the advent of modern capitalism, and how it evolved in the transition from agricultural to industrial capitalism. Looking into the future, they also address the challenges of today’s informational capitalism, which is characterized by the commodification of knowledge. Based on James’s work, the authors introduce the ‘correlative rights doctrine’ as an alternative to the remnant ‘property rights absolutism’ in the field of intellectual property law, but also beyond. With cross-border conflicts in who owns what having proliferated in the global age, investigations into the relational quality of property rights also matter for international lawyers, who are confronted with new subjects and objects of property, from international investment law to intellectual property law.
Law
Keywords: COMMONS; J.R.; international law; property rights

Markets in West Africa: Karl Polanyi, or what sort of social formation - Saul, Mahir (Market as Place and Space of Economic Exchange: Perspectives from Archaeology and Anthropology, 2018)
Anthropology
Keywords: West Africa; disembeddedness; economic anthropology; economic history; markets

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Biography; History; Economics
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate

Summoning Hunger: Polanyi, Piers Plowman, and the Labor Market - Epstein, Robert (Money, Commerce, and Economics in Late Medieval English Literature, 2018)
The “plowing of the half-acre” episode in Langland’s Piers Plowman includes a chilling passage in which Piers summons Hunger to force able but unwilling laborers to work the land. This chapter approaches the episode by way of the economic history of Karl Polanyi, whose critiques of free-market ideology are receiving renewed attention in the context of globalization and the international economic crisis. One of Polanyi’s key points is that the threat of starvation is a prerequisite to the institution of a true labor market—meaning that first the networks of collective support that peasants rely on for survival need to be undermined. The summoning of Hunger shows that Langland is actually more free market in his ideology than are the landowning supporters of the labor statutes.
English (literature);
Keywords: LANGLAND; William; Piers Plowman (book); economic history; globalization; hunger; threat of starvation